The Relationship between Body Shame and the Tendency towards Cosmetic Surgery among Female High School Students - Namjoo, Farhad; Namjoo , Atefe; Modabernejad, Zahrasadat; Modabernejad, Seyed Abbas (Journal of Personality and Psychosomatic Research (JPPR), 2023)
The purpose of this study was to determine the relationship between body shame and the inclination towards cosmetic surgery among female high school students in Shiraz. This applied research was conducted using a descriptive-correlational method. The study population included all female high school students in Shiraz, during the 2023-2024 academic year, from whom 350 individuals were selected through multi-stage cluster random sampling and studied. Data were collected using the Body Shame questionnaire by McKinley & Hyde (2001) and the Attitude Towards Cosmetic Surgery Scale by Swami et al. (2018). After data collection and extraction, participants' scores were analyzed using Pearson correlation coefficient and regression analysis. Regression test results showed that body shame has a significant effect on the inclination towards cosmetic surgery among female high school students in Shiraz (p